Evaluation of Progesterone and Estradiol in Sera and Tissue of Thyroid Patient (Iraqi Journal of Medical Sciences, 2016)
Background:Thyroid cancer is more common in subjects with blood group A and O. Estrogenic receptors in some cases of goiter were observed. Obesity is associated with increased risk of thyroid carcinoma possibly by mechanism of production of estrogenic steroids by adipose tissue. Objective:This study was done to determine and compare the progesterone and estradiol in sera and tissue of female patients with various thyroid disorders.Methods: In this prospective study, Serum and thyroid tissue homogenate were analyzed by measuring progesterone and estradiol in fifty normal healthy women volunteers as a control, in addition to ten patients with malignant thyroid nodules proved by histopathology, and thirty seven patients with benign thyroid nodules from March 2008 to August 2009 in Al-Kadhimiya Teaching Hospital and Al-Dirgham private hospital in Baghdad.Results:Serum estradiol and progesterone levels for both malignant and benign thyroid nodules patients were less than noticed in healthy control, while tissue estradiol and progesterone levels in malignant thyroid tumor were significantly higher than those in benign thyroid nodules.Conclusion:Tissue estradiol and progesterone levels can be used in the diagnosis and differentiation between malignant and benign thyroid nodules.Key word: progesterone, estradiol, Thyroid nodules